Global Conservation, National Park and Local Practices in Siberut Island, West Sumatera - Darmanto Darmanto (Jurnal Ilmu Kehutanan)
Siberut Island (West Sumatra) has high profile for conservation. This island of 403,500 ha has endemic species, ecological uniqueness and indigenous peoples assumed to have traditional ecological knowledge. Using ecological politics, this article will describe history of biodiversity conservation in Siberut. Discourse of Siberut conservation influenced by biological crisis narrative in the global context, scientific research and government policy. Conservation discourse was institutionalized during national parkestablishment in 1993 together with PKAT project and foreign debt from Asian Development Bank Nevertheless, conservation issue is not easy to implement in the local context and coherent with local practice. Indigenous people of Siberut interpret, articulate and produce meaning for conservation differently with other actors. The relationship between indigenous peoples and conservation issue has been characterized with negotiable features, ambiguity and instability. Meaning negotiation on how resources should be managed by actors with different interests resulted in dilemma of conservation.